Electrodeposition of amorphous Fe-Cr-P-Ni-C alloys. Morphological and structural characteristics - De Souza, Carlos Alberto C. [UNESP]; Carlos, Ivani A. [UNESP]; Bidoia, Ederio D. [UNESP] (Trans Tech Publications, 2002)
The effect of bath composition and electroplating conditions on structure, morphology and composition of amorphous Fe-Cr-P-Ni-C deposits on Cu substrate was investigated. The deposition efficiency of Fe-Ni-P-C alloy increased significantly with the addition of formic acid, but decreased with the addition of Cr to the plating bath. The increase of charge density activates the inclusion of Cr in the deposit. However, above a specific value of charge density, which depends on deposition current density, the Cr content in the deposit decreases. SEM analysis showed that the increase of Ni, Cr or charge deposition promotes susceptibility to microcracking.
Keywords: Alloys; Amorphous; Electrodeposition; Charge density; Composition; Current density; Deposits; Electroplating; Iron alloys; Microcracking; Morphology; Scanning electron microscopy; Amorphous alloys